KARAKTER MORFOLOGI DAN ANALISA DNA RAPD TANAMAN TUBA (Paraderris elliptica (Wall.) Adema)HASIL EKSPLORASIDI PROPINSI JAWA TIMUR - Sandra Wicaksono; Damanhuri Damanhuri; Darmawan Saptadi (BUANA SAINS, 2015)
The objective of the study was to determine the distribution of plants, morphologi plant characters and diversity of Tuba (Paraderris elliptica (Wall) Adema) as the results of explorationin the province of East Java. Exploration activities conducted by survey method (snowball sampling) based on the informationof "key informants" in East Java. Differences in morphology based on the qualitative and quantitative character. DNA RAPD analysis conducted on Laboratory of Biotechnology Faculty of Agriculture, Brawijaya University using five (5) primer OPN 4, OPN 11, OPN 15, OPN 16 and OPS 17. Tuba Plants distributed in Jember, Jombang and Sumenep with 17 accesions. The result of simple matching coefficient using dendogram with MVSP software version 3.2.1. There are diversity of plant susing DNA RAPD analysis